THE ROLE OF ENTREPRENEURSHIP LEARNING IN GROWING STUDENT ENTREPRENEURIAL INTEREST - Purna Irawan; Elce Purwandari; Liliany Purnama Ratu; Ahmad Khoirudin; Erwan Iskandar (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
Entrepreneurship is frequently defined as the act of developing something with the intention of adding value to the economy. The results of entrepreneurship can be found in both products and services. Lessons in entrepreneurship should be taught in higher institutions since they are predicted to be able to lower the high unemployment rate, particularly among educated people. In addition, innovative concepts and the most recent advancements are anticipated to surface to encourage student interest in entrepreneurship. MSMEs, the engine of the economy, are the entrepreneurial sector that is currently in the spotlight. Because the time required to manage a business is more flexible and can be self-regulated according to demands, so it doesn't conflict with study time, students can participate as MSME players. Using a sample of 56 students as respondents, this study intends to ascertain the contribution of entrepreneurship learning in generating interest in entrepreneurship among students at the Al-Azhaar Lubuklinggau Islamic Institute. A survey is the quantitative method that was used. By sending online surveys in the form of Google Forms with a Likert scale ranging from 1 to 4, data was gathered. Both quantitative and descriptive data analysis was done. According to the study's findings, entrepreneurship education helps students develop an interest in the field